Hubungan Antara Kepuasan Kerja dengan Motivasi Kerja pada Karyawan Sales Promotion Girl (SPG) Lapangan - Sehaningtyas, Ardhyaviana, Drs. Mohammad Amir, M. Si, Psi (2017)
Motivation is state in persons that encourages the desire of individuals to perform certain activities in order to achieve a goal. Understanding of job satisfaction can be explain briefly that job satisfaction is an assesssment or a reflection of the fellings of workers to their work. Job satisfaction will appear in the workers positive attitude to everything his work environment is facing and to his work. Job satisfaction and work motivation are often used together. The purpose of this study to determine whether there is a relationship between job satisfaction with work motivation, the subject of this study amounted to 50 people. The method used in this study is a quantitative method with measuring tools in the form of job satisfaction scales and work motivation scale. Data analysis technique used in this research is product momentcorrelation by using SPSS (Statistical Program for Social Sciene) 16.0 for window program. Based on the results of data analysis obtained correlation coefficient r = 0,379 sig,=0,003 (p<0,05) which means there is a very significant relationship between job satisfaction with work motivation. Job satisfaction variable included in high category, while work motivation enter into high category.